2021
DOI: 10.1111/jcmm.16920
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor 1‐alpha acts as a bridge factor for crosstalk between ERK1/2 and caspases in hypoxia‐induced apoptosis of cementoblasts

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Our present data revealed that compressive force at the magnitude of 2.4 gf/cm 2 triggered the HIF-1α expression. However, the mRNA levels decreased rapidly from 12 h stimulation possibly due to the initiation of apoptotic processes [2]. In this study, we clarified the expression of P. gingivalis PGN-induced PD-L1 and correlation of PD-L1/HIF-1α in cementoblasts.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our present data revealed that compressive force at the magnitude of 2.4 gf/cm 2 triggered the HIF-1α expression. However, the mRNA levels decreased rapidly from 12 h stimulation possibly due to the initiation of apoptotic processes [2]. In this study, we clarified the expression of P. gingivalis PGN-induced PD-L1 and correlation of PD-L1/HIF-1α in cementoblasts.…”
Section: Discussionmentioning
confidence: 80%
“…Compression is one hallmark of the specific microenvironments induced by orthodontic compressive force (CF) during orthodontic tooth movement (OTM), due to its capability to affect the cementoblasts homeostasis [1]. During OTM, compressive force triggers inflammatory osteoclastogenic and remodeling processes in the periodontal ligament (PDL) to further create an immune suppressive hypoxic microenvironment, which impairs the process of OTM [2]. The role of compressive force on the physiology of cementum has received increasing interest because orthodontically induced inflammatory root resorption (OIIRR) is a serious side effect of orthodontic tooth movement [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together from previous studies [ 12 15 ], the ribosomal 60S protein L22 ( RPL22 ), Peptidylprolyl isomerase B ( PPIB ), polymerase RNA II polypeptide A ( POLR2A ), Ribosomal protein, large, P0 ( RPLP0 ), glucuronidase, beta ( GUSB ), Actin-beta ( β-actin ), TATA-binding protein ( TBP ), ubiquitin C ( UBC ), glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), Tyrosine 3-monooxygenase/tryptophan 5-mono-oxygenase activate protein, zeta ( YWHAZ ), eukaryotic translation elongation factor 1 alpha 1 ( EEF1A1 ), Ribosomal protein L18 ( RPL ) and beta-5 class I ( TUBB ) were identified as reliable reference genes.…”
Section: Introductionmentioning
confidence: 88%
“…Cementoblasts, highly differentiated periodontal ligament (PDL) cells, are located on the cementum [ 13 ]. The apoptotic death of cementoblasts might contribute to orthodontically induced inflammatory root resorptions (OIIRR) during orthodontic tooth movement (OTM) [ 14 ]. One of the most distinctly activated apoptotic signals was the caspase (cysteinyl aspartate proteinases) family, which executes the extrinsic and intrinsic apoptosis pathways [ 15 ].…”
Section: Introductionmentioning
confidence: 99%